Multimedia Locawita Berbasis CTL untuk Meningkatkan Pemahaman Budaya Lokal Tulungagung bagi Siswa Kelas V SD - Riska Elies Ristiani; Karimatus Saidah; Wahid Ibnu Zaman (YASIN, 2026)
The low level of students’ understanding of Tulungagung local culture indicates the need for learning media that are contextual, engaging, and relevant to the learning experiences of elementary school students. This study aims to develop Contextual Teaching and Learning (CTL)-based LOCAWITA multimedia and to test its validity, practicality, and effectiveness in improving understanding of Tulungagung local culture among Grade V elementary school students. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 30 Grade V students of SDN 2 Sukorejo Wetan. Data were collected through expert validation sheets, teacher and student response questionnaires, and local culture understanding tests through pretest and posttest. The results showed that LOCAWITA multimedia obtained a validity level of 92%, categorized as very valid. The practicality of the media was indicated by teacher responses of 96% and student responses of 90%, categorized as very practical. The students’ average score increased from 60.83 in the pretest to 89.58 in the posttest. The Wilcoxon Signed Rank Test results showed a significance value of 0.000 (p < 0.05), indicating a significant increase in local culture understanding after the use of the media. The conclusion of this study affirms that CTL-based LOCAWITA multimedia is declared valid, practical, and effective for improving understanding of Tulungagung local culture among Grade V elementary school students. These findings imply the use of CTL-based multimedia as an alternative contextual learning medium that supports the preservation of local culture in elementary schools.